Financialization of housing, social policy and inequality - Fuchs, Pascal (Department of Philosophy, 2024)
The paper analyses the evidence and impact of housing financialization in South Africa. It gradually develops a mapping of the various interlinked characteristics of financialization and housing in the country. This mapping supports a structured discussion regarding the impact of housing financialization on income and wealth inequality trajectories. The identification of relevant characteristics of financialization follows a Marxist perspective on financialization, outlined by Fine (2013). Within this framework, the role of housing is understood in its capacity to absorb capital from a primary productive circuit of circulation into a secondary circuit for continued accumulation. Financialization, therefore, represents the increasing role of interest-bearing capital (IBC) and its prevalence in more fictitious forms. On this basis, the paper looks for evidence of financialization processes in the South African housing market and its implications for mortgage and housing access in low-income segments of society along with the role of public homeownership promotion policies. The analysis shows how the evidence of financialization processes, such as an increasingly relevant financial sector, short-term foreign investment inflows and increasing debt levels as well as the changing investment pattern of domestic companies impact the local housing market. In the presence of such financialization processes inequality aspects of housing are implicated through the highly exclusive mortgage access, growth of informal settlements, and repeating patterns of racially based spatial segregation. It also shows the limits of housing financialization in the country which include the lower levels of securitization of mortgage and the role of REITs in the residential property market. The various public housing policies of the past decades, which aimed at promoting homeownership for restorative justice and incentivizing private actor involvement in low-income mortgage markets, have not been able to cope with these negative trends. Increasing unemployment levels for low-skilled workers due to de-industrialization, shifting profits towards the financial sector, a volatile housing market and the dependence on generational wealth for housing access and asset-based welfare are outcomes of financialization which constitute a divergent impacts on income groups and exacerbate existing inequalities. These developments further challenge the effectiveness of the chosen public policies in the low-income housing market. Furthermore, the vigorous promotion of private actor involvement, such as banks and housing developers, by national and local governments and the broad privatization of public housing provided a basis for the further commodification and financialization of housing in South Africa. The replication and expansion of inequalities in South Africa in the past decades after its democratic transition can be seen as a social reproduction of uneven social class relations under financialized capitalism.